STUDY THE ADSORPTION OF CU(II) BY THE FUNGUS POLYPORUS SP POWDER AND CALCIUM ALGINATE BEADS WITH ENCAPSULATE FUNGUS POWDER. - Tapia H., N. (2012)
In the present work has been encapsulated the fungus Polyporussp powder (250mμ) with calcium alginate in the form of spherical pearls. We have studied the adsorption of the ions of Cu(II) by the fungus powder and by the pearls obtained from the fungus powder with calcium alginate in batch and in an ion exchange column.The optimal pH for the adsorption of the ions of Cu(II) is in the range of 4,5 to 5. The experimental data of the adsorption of Cu(II) are often described by the Langmuir model, it has achieved the following results: a) for the fungus powder the maximum adsorption capacity is qmax =23,15 mg/g , the constant of Langmuir is b=0,0663 , b) for the pearls of alginate with the fungus powder theqmax =5,385 mg/g and b=0,0089. The study of the adsorption of the pearls with the fungus powder in a packed column of ion exchange show that these pearls have a good capacity for the removal of the ions of Cu(II).